THE INFLUENCE OF BRAND EXPERIENCE ON BRAND LOYALTY THROUGH BRAND LOVE IN ACER BRAND LAPTOP USERS IN MEDAN CITY - Henty Trisna Gulo; Hafizah; Sunaryo (Jurnal Ekonomi, 2023)
This study aims to determine the effect of brand experience on brand love. To determine the effect of brand experience and brand love on brand loyalty partially. To find out the effect of brand experience on brand loyalty through brand love for Aceh Laptop Users in Medan City. The population in this study is not known with certainty and uses the MOE formula. So, the sample used in this study is 100 people. The sampling technique used was purposive sampling. The analysis technique used is path analysis. The results showed that brand experience had a positive and significant effect on brand loyalty, brand love had a positive and significant effect on brand loyalty, brand experience had a positive and significant effect on brand love, brand experience had a positive and significant effect on brand loyalty through brand love.